Tracking technology for tourist behavior - Sunaryo, Budi; Rusdi, Jack Febrian; Salam, Sazilah; Abu, Nor Azman; Sabar, Muhamad; Agustina, Nova (2023)
Tourism is the fastest growing sector in the world, and the key to the success of tourism is understanding tourist behavior. Unfortunately, research in terms of information technology, especially in terms of tracking tourist behavior, receives little attention from researchers. This study aims to provide various potential alternative technologies to be used in researching tourist behavior through information technology. This study was conducted through a literature study. This article produces various techniques used in tracking the behavior of tourist movements, especially to support the growth of the tourism sector through the use of technology.